Bridging science and spirituality: the intersection of religion and public health in the COVID-19 pandemic - Ayub, Shahana; Anugwom, Gibson O.; Basiru, Tajudeen; Sachdeva, Vishi; Muhammad, Nazar; Bachu, Anil; Trudeau, Maxwell; Gulati, Gazal; Sullivan, Amanda; Ahmed, Saeed; Jain, Lakshit (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic has had global impacts on social interactions and religious activities, leading to a complex relationship between religion and public health policies. This article reviews impact of the COVID-19 pandemic on religious activities and beliefs in relation to the spread of the virus, as well as the potential of religious leaders and faith communities in mitigating the impact of the pandemic through public health measures and community engagement. Methods A literature review was conducted using PubMed and Google Scholar, with search terms including “religion,” “COVID-19,” “pandemic,” “coronavirus,” and “spirituality.” We included English articles published between January 2020 and September 2022, focusing on intersection of religion and COVID-19. Results We identified two main themes emerging, with the selected 32 studies divided in 15 studies focused on the relationship between religious practices, beliefs, and the spread of COVID-19, while 17 studies explored the role of religious leaders and faith communities in coping with and mitigating the impact of COVID-19. Religious activities were found to correlate with virus spread, particularly in early days of the pandemic. The relationship between religiosity and adherence to government guidelines was mixed, with some studies suggesting increased religiosity contributed to misconceptions about the virus and resistance to restrictions. Religious beliefs were also associated with vaccine hesitancy, particularly conservative religious beliefs. On the other hand, religious leaders and communities played a crucial role in adapting to COVID-19 measures, maintaining a sense of belonging, fostering emotional resilience, and upholding compliance with public health measures. The importance of collaboration between religious leaders, institutions, and public health officials in addressing the pandemic was emphasized. Conclusions This review highlights the essential role of religious leaders, faith-based organizations, and faith communities in promoting education, preparedness, and response efforts during the COVID-19 pandemic. Engaging with religious leaders and communities can improve pandemic control and prevention efforts. Collaboration between religious leaders, governments, and healthcare professionals is necessary to combat vaccine hesitancy and ensure successful COVID-19 vaccination campaigns. The insights from this review can guide future research, policy development, and public health interventions to minimize the impact of the pandemic and improve outcomes for individuals and communities affected.